KINERJA PEGAWAI DALAM PELAYANAN PUBLIK PADA DINAS PERPUSTKAAN DAN KEARSIPAN KABUPATEN LUWU - Putri, Muchlisa Eka; Malik, Ihyani; Haerana, Haerana (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
This research aims to determine the performance of employees in public services at the Luwu Regency Library and Archives Service. This type of research uses qualitative methods, data collection techniques through observation, interviews and documentation. The results of the research show that: (1). Professionalism, in carrying out the duties of the Luwu Regency library and archives service staff, they have abilities that are in accordance with their respective main duties and functions in providing services to visitors. (2 Proportional, employees carry out their duties based on their respective duties so that there is no overlap between one field and another (3). Accountable, decision making has been carried out transparently, identifying problems that occur. (4 Effective and Efficient , the application of innovation that makes visitors interested in coming to the library